AQUIFER SUCEPTIBILITY AND AGRICULTURAL ACTIVITIES EFFECT ON WATER QUALITY IN SEMIARID ZONE: EL MA LABIOD PLAIN, NORTH EAST OF ALGERIA - Samoun FATAH (Stefan cel Mare University of Suceava, 2020)
For more than three decades, many agrarian systems have been intensified in an attempt to reduce the widening gap in food deprivation. The concern to feed the population has meant that the consequences have not been well studied, especially the degradation of groundwater, which was not yet among the issues discussed in developing countries. The study of piezometric measurements shows that the groundwater level of the plain of El Ma Labiod decreases on average by one meter per year. The chemical analysis shows that few of the 40 representative water points sampled, in the study area, exceed drinking water standards for nitrate and chloride concentrations, making 5 wells unsuitable for drinking water production and 8 others unfit for human consumption without prior treatment. It was found that Nitrate was the main component that degrades the quality of groundwater. The application of the DRASTIC and GOD methods to estimate the susceptibility of aquifers has made it possible to highlight three classes of vulnerability from very low to moderate. The mapped results using GIS data and ArcGis tools show a large similarity in the spatial distribution of vulnerability classes and the alteration of water quality. The purpose of this study is to take stock of the state of groundwater and create a basic document for decision-making to ensure healthy environment development in the study area.